1979
DOI: 10.1111/j.1471-4159.1979.tb05173.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Blood‐brain Barrier Transport of Pyruvate, Lactate and Glucose in Suckling, Weanling and Adult Rats

Abstract: The kinetics of the uptake from blood to brain of pyruvate, lactate and glucose have been determined in rats of different ages. The carotid artery single injection technique was used in animals anaesthetized with pentobarbital. The rates of influx for each substrate were determined over a range of concentrations for the different age-groups. Data were analysed in terms of the Michaelis-Menten equation with a component to allow for non-saturable diffusion. Values are given for K , . V,,, and K,. In suckling rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
193
2
2

Year Published

1982
1982
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(213 citation statements)
references
References 32 publications
(11 reference statements)
16
193
2
2
Order By: Relevance
“…There appears to be a facilitated transport system for lactate in adult rats (Oldendorf, 1973;Cremer et al, 1976Cremer et al, , 1979 but this has been less reproducibly demonstrated in adult dogs (Crone and Sorensen, 1970;Nemoto et al, 1974). Studies have suggested that the fetus or newborn rodent may actually have an increased capacity for lactate transport across the blood-brain barrier (Cremer et aI., 1976) in some neonatal species but we could not find evi dence for such a capacity in the fetal sheep (unpub lished observations) using venous outflow indicator dilution methodology.…”
Section: Controlcontrasting
confidence: 54%
“…There appears to be a facilitated transport system for lactate in adult rats (Oldendorf, 1973;Cremer et al, 1976Cremer et al, , 1979 but this has been less reproducibly demonstrated in adult dogs (Crone and Sorensen, 1970;Nemoto et al, 1974). Studies have suggested that the fetus or newborn rodent may actually have an increased capacity for lactate transport across the blood-brain barrier (Cremer et aI., 1976) in some neonatal species but we could not find evi dence for such a capacity in the fetal sheep (unpub lished observations) using venous outflow indicator dilution methodology.…”
Section: Controlcontrasting
confidence: 54%
“…19,20) It is thought that the induction of a lactate uptake system in the brain is to allow the use of the lactate in milk. In the deficient mice, MCT1 expression in the brain reached its highest levels at P14, the same levels as in the wild type (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ketone bodies formed by the hepatic oxidation of milk-derived fat are also significant energy substrates for the brain during the preweaning period in rodents (23,39). Lactate and ketone body utilization in the brain is very high during the suckling period but decreases after weaning to reach adult values (1,2,14,21,23). In parallel with this energy utility, a higher expression of MCT1 in the microvessels of the brain is observed during suckling in rodents (8,19,25) and declines with weaning, being accompanied by the predominant expression of GLUT1 in the postweaning period (39).…”
Section: Switching Of Transporters From Mct1 To Glut1 During Developimentioning
confidence: 99%